Implementasi Ekstrakurikuler Sie Kerohanian Islam Membentuk Karakter Religius Peserta Didik Di SMA Negeri 1 Kediri - Lailatul Maulidiyah; Hamam; Nasrul Syarif (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The research aims to (1) Analyze the implementation of the Sie Kerohanian Islam (SKIS’T) extracurricular activities at SMAN 1 Kediri, (2) Examine the contribution of SKIS’T activities to shaping students’ religious character, and (3) Identify the supporting and inhibiting factors in its implementation. A descriptive qualitative approach was employed, with data analyzed using the Miles and Huberman model.The findings reveal that (1) SKIS’T activities are conducted outside regular class hours through daily programs (Qur’anic literacy and congregational Dhuhr prayer), weekly programs (Friday charity/infaq and congregational Friday prayer), annual programs (commemoration of Islamic holidays, grand tabligh, and Ramadan retreat), and Islamic arts (Majlis Seni Islam and banjari group); (2) SKIS’T significantly contributes to building students’ religious character, evidenced by increased spiritual awareness, discipline in worship, and social care; (3) supporting factors include alignment with the school’s MUSTIKA vision, strong support from school management and teachers, committed administrators, student enthusiasm, adequate facilities, and sufficient funding, while inhibiting factors involve lack of interest among some students and occasional miscommunication among administrators.In conclusion, the structured SKIS’T extracurricular at SMAN 1 Kediri effectively fosters students’ religious character. It is recommended that the school continue addressing existing obstacles to optimize the program’s impact.